CODESRIA Bulletin Online, No. 14, December 2024 - Thandika Mkandawire and the African Intellectual Decolonisation Movement - Zeleza, Paul Tiyambe (CODESRIA Bulletin, 2024)
Keynote Address, New Directions in African Political Economy, Scholarly Conference, The Africa Institute, Global Studies University, Sharjah, United Arab Emirates, 14–16 November 2024. It is a profound honour to deliver the keynote address at this landmark conference on New Directions in African Political Economy, hosted by The Africa Institute at Global Studies University, Sharjah, in celebration of the life and legacy of the incomparable Professor Thandika Mkandawire. When the invitation arrived, I accepted without hesitation—not only because of my position on the institute’s Advisory Board but also for the rare privilege of gathering with those who knew and loved Thandika best: his friends, colleagues, mentees and students. Above all, this moment allows me to pay tribute to a man I revered as both a friend and mentor, a luminous intellect whose work reshaped our understanding of Africa’s place in the world. Thandika was more than a scholar: he was a visionary, a humanist and one of the continent’s most profound voices. To honour him today is to affirm the enduring power of his ideas and the deep well of inspiration he left us, urging us always towards a more just and equitable future. Thandika Mkandawire (1940–2020) was a towering intellectual giant, whose work embodied the historic and humanistic mission of African nationalism: to liberate African societies and academic communities from the enduring chains of colonial and neocolonial economic and epistemic dependency. His illustrious career spanned continents, disciplines and institutions, leaving an indelible imprint on African and global academic landscapes. As an economist, social theorist and visionary institution-builder, Mkandawire devoted his life to decolonising knowledge, reimagining development and championing democracy. Yet, beyond his formidable scholarship, he was a mentor, a leader and a profoundly humane presence whose warmth and generosity illuminated countless lives. Having had the privilege of knowing him personally and marvelling at his extraordinary intellect, I am convinced that Mkandawire’s scholarly legacy is an intellectual treasure trove—an enduring wellspring of insight and inspiration for current and future generations of African thinkers on the continent and in the diaspora. This presentation examines seven pivotal dimensions of his life and work, enriched by reflections from his peers, mentees and admirers, as so powerfully captured in the special issue of CODESRIA Bulletin (Nos 2 & 3, 2020) and other heartfelt tributes published since his passing. Influences: Shaping an Intellectual Giant Mkandawire’s intellectual journey was profoundly shaped by a confluence of personal experiences, historical events and academic encounters. Born in 1940 in colonial Zimbabwe to a Malawian father and Zimbabwean mother, Mkandawire’s early life exposed him to the stark realities of colonialism and systemic racial inequalities. His childhood in Zambia, where his father worked as a migrant labourer, further deepened his understanding of structural injustice. The colonial labour system, with its exclusion of Africans from skilled and well-paying jobs, marked him and fostered a lifelong commitment to challenging inequitable structures. Mkandawire’s secondary education in Malawi was a pivotal period in his intellectual formation. Unlike the entrenched racial hierarchies he had seen in Zambia, in Malawi he met an exceptionally underdeveloped colony that served as a regional labour reserve. This exposure to the variability of colonial experiences sparked his curiosity about the broader sociopolitical dynamics shaping African societies. His burgeoning political consciousness found an outlet in journalism, where he began criticising colonial rule and its injustices. Writing for Malawian newspapers, he voiced opposition to the authoritarian tendencies of the emerging postcolonial dictatorship under Hastings Kamuzu Banda, which led to his imprisonment and subsequent exile. His time in exile was transformative. Mkandawire pursued higher education in the United States during the Civil Rights Movement, a period marked by intense political activism and intellectual ferment. The racial struggles and anticolonial discourses of the time resonated deeply with him. He was particularly influenced by radical political economists such as Gunnar Myrdal and Arthur Lewis, whose works challenged orthodox economic theories and emphasised the importance of state-led development. The nationalist writings of Kwame Nkrumah and Julius Nyerere further solidified his commitment to African liberation and development. Another formative period was his time in Sweden, where he was granted asylum after his passport was revoked by the Banda regime. There, Mkandawire was introduced to the Nordic model of social democracy, which heavily influenced his thinking on developmental states and social policy. The Nordic experience showed the possibility of combining economic growth with social equity, a lesson he believed held immense relevance for Africa. Sweden also gave him an academic home, where he taught economics and began developing his ideas on development and governance. Mkandawire’s intellectual influences were not confined to economics and political science. He had a voracious appetite for knowledge, drawing insights from history, sociology, cultural studies and the arts, including music and literature. This interdisciplinary approach enriched his scholarship, allowing him to engage with complex issues from multiple perspectives. His broad intellectual foundation, combined with his lived experiences, shaped him into a thinker who could bridge theory and practice, local realities and global discourses. Nationalism and Pan-Africanism: Foundations of Intellectual and Political Commitment Nationalism and Pan-Africanism were central to Mkandawire’s intellectual and political commitments. His early engagement with nationalist movements in Malawi reflected his belief in the transformative power of self-determination. Even as a young journalist, he was deeply involved in the anticolonial struggle, condemning the colonial authorities and advocating for African liberation. This commitment to nationalism, however, was not uncritical. Mkandawire was acutely aware of the tensions between nationalist ideals and the realities of post-independence governance, where authoritarianism and elite capture often undermined the broader goals of liberation. In exile, Mkandawire’s commitment to Pan-Africanism deepened as he immersed himself in the Civil Rights Movement in the United States. He came to view the struggles for independence not as isolated national events but as part of a broader continental movement for liberation and unity and for the liberation of global Africa. His Pan-Africanist vision found institutional expression in his leadership at the Council for the Development of Social Science Research in Africa (CODESRIA). Under his stewardship, CODESRIA became a vibrant platform for intellectual collaboration across linguistic and regional divides, fostering a sense of unity among African scholars. Mkandawire’s Pan-Africanism was also evident in his scholarship. He wrote extensively on the role of nationalism in state-building and identity formation. In his influential essay ‘African Intellectuals and Nationalism’, he explored the complex relationship between intellectuals and nationalist movements. He argued that although intellectuals played a crucial role in articulating nationalist visions, they often found themselves in conflict with post-independence regimes that prioritised political loyalty over critical engagement. Mkandawire disagreed with Marxist scholarship’s dismissal of nationalism as a regressive force, asserting that nationalism had been a vital unifying mechanism in the face of colonial fragmentation. Throughout his career, Mkandawire remained a staunch advocate for African unity and cooperation. He believed that the continent’s challenges—economic underdevelopment, political instability and social inequality—could be effectively addressed only through collective action. His Pan-Africanist ideals extended beyond the political realm to encompass intellectual and cultural dimensions, advocating for the decolonisation of knowledge and the promotion of African perspectives in global discourses. His views also resonated with the broader project of reconnecting African intellectuals with the Pan-African ideals of earlier generations, demonstrating that these aspirations remained critical in addressing contemporary issues of underdevelopment and disempowerment. Career Trajectory: From Journalism to Global Leadership Mkandawire’s career trajectory was marked by a seamless integration of intellectual rigour, institutional leadership and a deep commitment to social justice. As a journalist in Malawi, his sharp criticism of colonial rule and post-independence authoritarianism earned him both acclaim and persecution. His exile marked a turning point, as he transitioned from journalism to academia, eventually becoming a leading figure in the field of development economics. In the United States, Mkandawire studied economics, gaining insights into the interplay between politics and development. His academic journey continued in Sweden, where he became a lecturer in economics at the University of Stockholm. This period was crucial for the development of his ideas on state-led development and social policy, which would later become central themes in his work. Mkandawire’s return to Africa in the 1980s marked a new phase in his career. He took on a leadership role at the Zimbabwe Institute of Development Studies, where he helped shape the institute’s research agenda during Zimbabwe’s early post-independence years. This experience underscored his belief in the importance of building strong, autonomous research institutions capable of producing context-specific knowledge. His most significant contributions, however, came during his tenure as Executive Secretary of CODESRIA, from 1986 to 1996. Mkandawire transformed CODESRIA into a leading Pan- African research organisation, providing a critical platform for scholars grappling with the socioeconomic challenges of the time. Under his leadership, CODESRIA expanded its programmes, marked by the establishment of national and multinational working groups that fostered collaborative, cross- disciplinary research. Recognising the importance of intellectual continuity in the face of underfunded universities and restrictive political environments, he prioritised nurturing future scholars by providing research grants and mentorship for Master’s students, thus ensuring a sustainable pipeline of African intellectual leadership. Other initiatives included the launch of Democratic Governance and Gender Institutes. In 1998, Mkandawire was appointed Director of the United Nations Research Institute for Social Development (UNRISD), where he oversaw pioneering research on social policy and governance in developing countries. His tenure at UNRISD, where he used the platform to advocate for policies that prioritised social equity and sustainable development, further cemented his reputation as a global thought leader. There, Mkandawire reinforced his earlier insights, showing how international financial structures often marginalised the specific developmental needs of African states. Notably, he invited me to join a team of nine feminist scholars, as one of two men, to produce a landmark report marking the tenth anniversary of the 1995 UN Beijing Women’s Conference. The resulting publication, Gender Equality: Striving for Justice in an Unequal World, reflected his commitment to gender equity as a cornerstone of social justice and development. Mkandawire’s final academic role was as the inaugural Chair in African Development at the London School of Economics (LSE), from 2009 until his passing in 2020. At LSE, he continued to mentor a new generation of scholars while also engaging in public debates on development and governance. His work at LSE was characterised by a continued focus on the structural transformation of African economies and the role of social policy in promoting inclusive growth. Throughout his career, Mkandawire remained committed to the principles of intellectual autonomy and academic freedom. He was a staunch defender of the independence of the institutions he led, often standing up to powerful external actors to ensure that African scholars could pursue their research free from undue influence. His career trajectory, marked by a combination of scholarly excellence and visionary leadership, is a powerful testament to his enduring commitment to development economics and Pan-African scholarship. Decolonising Knowledge: Asserting African Intellectual Sovereignty Thandika Mkandawire’s advocacy for the decolonisation of knowledge was both a critique of entrenched academic hierarchies and a clarion call for the intellectual sovereignty of African scholars. He believed that the subordination of African knowledge systems to Western epistemic hegemony was one of the most significant barriers to genuine development on the continent. His life’s work was deeply rooted in the conviction that African scholars must play a central role in shaping the narratives and policies that affect their societies. For Mkandawire, decolonising knowledge was not merely an academic exercise but a vital step in reclaiming agency over Africa’s development trajectory. Mkandawire consistently condemned the global academic system for its marginalisation of African voices. He highlighted the structural biases inherent in scholarly publishing, including the dominance of Euro-American journals and the exclusion of African perspectives from mainstream discourses. In his view, this exclusion perpetuated a distorted and incomplete understanding of African realities. He pointed to the widespread practice of ‘intellectual appropriation’, which often analysed African data and experiences through frameworks that disregarded the continent’s unique historical and cultural contexts. A central theme in Mkandawire’s work was the critique of ‘institutional monocropping’, a term he used to describe the imposition of uniform institutional models on African states by international financial institutions. These models, derived from Western experiences, often failed to account for the diverse sociopolitical and economic realities of African societies. Mkandawire argued that structural adjustment programmes (SAPs) epitomised this approach, undermining state capacity and development strategies tailored to local needs. He likened these programmes to a form of intellectual colonisation, because they compelled African states to adopt externally prescribed solutions that often deepened their dependency. Mkandawire’s principled stance on intellectual autonomy was made vividly clear in an encounter with a World Bank delegation in 1992. The delegation proposed a research project, with a predefined design and methodology. Mkandawire firmly rejected this approach, insisting that CODESRIA would accept funding and a broad thematic focus, but the design, execution and management of the project had to remain under African control. He emphasised that while the Bank could audit financial records, it would have no say in the intellectual process. This insistence on sovereignty in knowledge production led the World Bank to withdraw, and underscores Mkandawire’s unwavering dedication to preserving the independence and integrity of African scholarship. Mkandawire also highlighted the exploitative dynamics of North–South research collaborations. He rejected the ‘data extraction’ model, which often relegated African researchers to secondary roles as ‘academic maids’ in projects led by scholars from the global North. He emphasised that African scholars must not only collect data but also be at the forefront of theorising and interpreting their findings to shape knowledge production. Mkandawire called for equitable partnerships that recognised and valued the intellectual contributions of African researchers, insisting on the importance of ethical research practices that empowered African institutions. His vision extended beyond mere reform: it sought to reimagine scholarly collaboration as a space for mutual respect and genuine exchange, where African scholars could assert their intellectual sovereignty. For Mkandawire, decolonisation was not merely about challenging Eurocentric paradigms, it also required African scholars to actively reference and engage with the work of their peers on the continent. He believed that building a robust and interconnected African intellectual community was essential for producing knowledge rooted in local realities. Additionally, Mkandawire advocated for serious engagement with scholarship from Asia and Latin America, recognising the shared histories of colonialism and underdevelopment across the global South. By drawing from these diverse knowledge systems, African scholars could develop more nuanced and comparative frameworks that enriched global academic discourses and advanced the collective struggle for epistemic sovereignty. Through his leadership and scholarship, Mkandawire laid the groundwork for a decolonised intellectual landscape by championing initiatives that sought to dismantle the structural and epistemic hierarchies entrenched in the global academy. His tenure at institutions like CODESRIA and UNRISD was marked by efforts to empower African scholars to define their research agendas, theorise from their own historical and social contexts and publish on platforms that amplified their voices. He understood that decolonising knowledge required a dual approach: challenging the external dominance of Western epistemologies while fostering a vibrant, self-sustaining intellectual community within Africa. This manifested in several concrete ways. At CODESRIA, Mkandawire instituted programmes such as the national and multinational working groups noted earlier, which provided funding and networks for African researchers to collaborate on projects of national and regional relevance. He also emphasised the importance of publishing in African journals to counter the exclusion of African perspectives from mainstream academic outlets. Moreover, Mkandawire was a staunch critic of the academic gatekeeping practices that marginalised African scholars, such as the privileging of Western theoretical frameworks and methodologies over Indigenous ones. Mkandawire’s vision differed in some ways from the contemporary decoloniality movement. While both aimed to dismantle epistemic hierarchies, Mkandawire focused on empowering African institutions and scholars to produce knowledge that could reshape global discourses. He saw value in selectively engaging with Western theories, not to mimic them but to adapt and critique them in ways that served African realities. In contrast, many contemporary decoloniality scholars emphasise a more radical epistemic disobedience, advocating for the complete rejection of Western paradigms in favour of Indigenous knowledge systems. Mkandawire’s approach also extended beyond the African continent. He advocated for horizontal solidarity with scholars from Asia and Latin America, recognising that the challenges of epistemic domination were not unique to Africa. He believed in building a South–South intellectual alliance that could produce comparative frameworks, offering alternative global perspectives rooted in shared experiences of colonialism and underdevelopment. At the same time, Mkandawire maintained a pragmatic approach to decolonisation, focusing on practical steps to build intellectual capacity and autonomy in African institutions. Under his leadership, CODESRIA expanded its publications programme. It collaborated with other academic publishers on the continent to establish the African Books Collective (ABC) in 1989, an African-owned, worldwide marketing and distribution outlet for books from Africa, and the African Publishers Network (APNET), founded in 1992 to strengthen Indigenous publishing. Mkandawire’s approach contrasts with that of some contemporary decoloniality scholars, who emphasise the symbolic and cultural dimensions of decolonisation, such as rethinking curricula and revisiting the canon. For Mkandawire, the ultimate goal was to ensure that African scholars were not just participants but leaders in the global production of knowledge, shaping policies and theories that resonated far beyond the continent. His vision for intellectual sovereignty continues to light the way, offering a nuanced framework for addressing the epistemic injustices that persist in the global knowledge economy. By advocating for a decolonised yet globally engaged intellectual landscape, Mkandawire set a precedent for how African scholarship can thrive in a world still grappling with the legacies of colonialism. Reconceptualising Development: From Dependency to Transformation One of Mkandawire’s most significant contributions was his redefinition of development as a holistic and multidimensional process, not merely a matter of economic growth but of structural transformation and social progress. He argued that development must be context-specific, tailored to the unique historical, social and cultural realities of each country. It was not just about increasing GDP or implementing market reforms, it was also about fostering human wellbeing, reducing inequalities and building resilient institutions. He emphasised the centrality of the state in orchestrating development, rejecting the neoliberal assertion that markets alone could deliver growth and equity. He rejected the reductionist approach of international financial institutions, which often treated development as a technocratic exercise, divorced from its political and social underpinnings. Mkandawire’s conceptualisation of the ‘developmental state’ was a cornerstone of his scholarship. He argued that a developmental state was not merely one that pursued economic growth but one that actively sought to transform its economic structure through industrialisation, technological innovation and human capital development. Mkandawire identified the capacity for strategic state intervention as the defining characteristic of developmental states. This required not only competent bureaucracies but also a social contract between the state and its citizens, where the benefits of development were widely shared, fostering legitimacy and trust. He debunked the myth that African states were inherently incapable of being developmental— what he called the ‘impossibility arguments’—pointing to examples from the immediate post- independence period, when many countries demonstrated remarkable developmental ambitions. During this period, states invested heavily in education, healthcare and infrastructure, achieving impressive growth rates. However, the imposition of SAPs in the 1980s and 1990s undermined these efforts. These programmes stripped states of their capacity to manage their economies, prioritising fiscal austerity and market liberalisation over long-term development goals. Mkandawire highlighted how these externally imposed policies eroded the foundations of developmental states, leaving them vulnerable to economic shocks and perpetuating dependency. CODESRIA, together with the UN Economic Commission for Africa (UNECA) under Adebayo Adedeji, waged fierce policy and intellectual attacks against SAPs, highlighting their devastating social and economic impacts, which dismantled public services, decimated local industries and exacerbated poverty and inequality. Through rigorous research and advocacy, these institutions provided a counter-narrative to the dominant neoliberal orthodoxy, emphasising the need for development strategies that preserved state autonomy and prioritised the wellbeing of African populations. Mkandawire underscored the importance of learning from the developmental successes of East Asia and Scandinavia, emphasising that developmental states are made through deliberate policy choices and institutional reforms. As key lessons, he highlighted East Asia’s rapid industrialisation and Scandinavia’s integration of social policies with economic strategies. However, he cautioned against wholesale imitation, advocating for African states to adapt these lessons to their unique contexts. By doing so, they could forge development paths that balanced economic growth with social equity. In his vision, social policy was an integral part of the developmental state. Mkandawire rejected the narrow view that social policies were merely safety nets for the poor. Instead, he championed ‘transformative social policy’, which aimed to address the root causes of poverty and inequality. He argued that investments in education, healthcare and social infrastructure were not just morally imperative but economically strategic, because they enhanced productivity, fostered social cohesion and laid the groundwork for sustained growth. Mkandawire’s critique of the development industry extended to the valorisation of the informal sector and microfinance as panaceas for poverty. While acknowledging the importance of the informal sector, he cautioned against romanticising it as a substitute for formal employment and industrialisation. He argued that microfinance, often hailed as a revolutionary tool for poverty alleviation, did little to address structural inequalities and could sometimes exacerbate them by burdening the poor with debt. Instead, he called for bold, state-led interventions that could drive systemic change and create pathways to formal employment and sustainable livelihoods. Through his scholarship, Mkandawire offered a visionary framework for reimagining development in Africa. He urged policymakers and scholars to move beyond superficial metrics and adopt a holistic, people-centred approach that prioritised equity, sustainability and self-determination. His ideas resonated with several African leaders, including those of Ethiopia, Rwanda and Botswana, who sought to implement state-led development strategies and transformative social policies. These leaders drew on Mkandawire’s insights to craft policies aimed at fostering economic growth, reducing poverty and building resilient institutions. His ideas remain influential, providing a critical lens through which to analyse and address the complex challenges of development in the global South. Democracy and Development: A Symbiotic Relationship Mkandawire was a steadfast advocate for the symbiotic relationship between democracy and development. He rejected the authoritarian developmental state model of East Asia, which argued that economic growth required suppressing democratic freedoms. Instead, he championed the concept of the ‘democratic developmental state’, which integrates the developmental ambitions of state-led policies with the principles of democratic governance. Mkandawire argued that democracy and development were mutually reinforcing. Democratic institutions, he believed, offered essential mechanisms for accountability, transparency and inclusivity. By fostering public participation and ensuring that citizens had a voice in policymaking, democratic governance enhanced the legitimacy and effectiveness of development policies. Mkandawire contended that inclusive governance structures were better equipped to manage social conflicts, build consensus around development priorities and ensure that growth benefited all segments of society. A significant focus of Mkandawire’s critique was the concept of ‘choiceless democracies’. This term referred to African democracies constrained by structural adjustment programmes, which limited their policy options and undermined their developmental goals. He argued that these programmes eroded the social contract between governments and their citizens, because they often imposed austerity measures that worsened inequality and poverty. Mkandawire called for policy frameworks that allowed democratically elected governments to pursue development strategies aligned with their citizens’ aspirations. Mkandawire also emphasised the intrinsic value of democracy. Whereas some scholars viewed democracy primarily as a means to achieve better development outcomes, Mkandawire insisted that democracy was worth pursuing for its own sake. He saw it as a fundamental expression of human dignity and a critical safeguard against tyranny and oppression. His work highlighted the importance of protecting democratic institutions and practices, even in contexts where the developmental benefits might not be immediately apparent. Through his advocacy for democratic developmental states, Mkandawire offered a compelling vision for governance in Africa. He demonstrated that economic and political freedoms could coexist and mutually reinforce each other, providing a foundation for sustainable and inclusive development. His insights continue to inform debates on governance and development, challenging the false dichotomy between political freedom and economic progress. The Man and His Legacy: A Mentor, Leader and Visionary Thandika Mkandawire’s intellectual contributions were matched by his exceptional personal qualities. He was widely regarded as a mentor, a leader and a visionary whose warmth, humility and generosity left a deep impression on those who knew him. His colleagues and students often spoke of his ability to inspire and challenge them, providing guidance and encouragement while fostering a spirit of intellectual curiosity and critical thinking. Mkandawire’s leadership at CODESRIA and UNRISD was transformative. At CODESRIA, he nurtured a culture of intellectual rigour and collaboration, creating a platform for African scholars to engage in critical debates and produce impactful research. He was committed to ensuring that CODESRIA remained an autonomous and inclusive institution, open to scholars from diverse disciplinary and regional backgrounds. His insistence on maintaining the organisation’s intellectual and financial independence was a testament to his unwavering belief in the importance of African agency in knowledge production. As a mentor, Mkandawire was deeply invested in the success of his students and colleagues. He took the time to provide detailed feedback on their work, often sparking new perspectives through his incisive critiques. His mentorship was characterised by an exceptional ability to balance constructive criticism with encouragement, enabling young scholars to refine their intellectual pursuits without losing confidence. Many of his mentees, now leading scholars and practitioners, credit him with shaping their careers and intellectual trajectories. Mkandawire’s personal warmth and humility made him an approachable figure despite his towering intellect and global stature. He believed in the power of community and collaboration, often creating informal spaces for intellectual exchange. Whether in conference corridors, over meals, or in late-night discussions, he engaged deeply with others, always listening attentively and offering thoughtful insights. His laughter, humour and ability to find joy in even the most challenging circumstances are fondly remembered by all who interacted with him. Beyond his immediate circles, Mkandawire’s influence extended to the global academic and policy communities. His work resonated across disciplines, challenging scholars and policymakers to rethink conventional approaches to development, governance and social policy. His advocacy for intellectual autonomy and his critiques of external interventions in African development provided a critical framework for understanding the continent’s challenges and opportunities. Mkandawire’s legacy is enshrined not only in his scholarly contributions but also in the institutions he helped build and the countless lives he touched. His tenure at CODESRIA, UNRISD and the London School of Economics exemplified his commitment to creating spaces where African scholars could thrive and contribute meaningfully to global discourses. His work at these institutions reflected his deep-seated belief in the transformative power of collective intellectual endeavour. By fostering environments where critical thinking and rigorous scholarship could flourish, Mkandawire helped to shape the intellectual trajectories of a generation of African scholars and policymakers. Mkandawire’s legacy extends beyond his immediate contributions to institutional development and academic discourse. He was a tireless advocate for the integration of African voices into global debates on development and governance. His vision of an intellectually sovereign Africa was not confined to academic institutions but extended to policymaking and international cooperation. He consistently argued that Africa’s development challenges could be effectively addressed only if its unique perspectives and experiences were central to the global development agenda. In his personal and professional life, Mkandawire embodied the values he espoused. He was a mentor who invested deeply in his relationships with students and colleagues, offering not only intellectual guidance but also personal support and encouragement. His leadership style was characterised by inclusivity and collaboration, reflecting his belief that the most significant breakthroughs in knowledge and policy emerge from collective effort. A Vision for the Future Thandika Mkandawire’s work is still a vital resource for addressing the complex challenges of our time. His insights into the interplay between democracy, development and social policy offer a framework for reimagining governance and economic transformation in Africa and beyond. His call for the decolonisation of knowledge production continues to inspire efforts to democratise academic and policy spaces, ensuring that diverse perspectives inform global debates. As Africa navigates the twenty-first century, Mkandawire’s vision for a just, equitable and prosperous continent is a guiding light. His emphasis on intellectual sovereignty, social policy as a tool for transformation and the symbiotic relationship between democracy and development offers a roadmap for achieving sustainable and inclusive growth. His legacy challenges current and future generations to continue the work of dismantling epistemic and structural barriers, fostering innovation and promoting justice. In remembering Thandika Mkandawire, we honour a life dedicated to the pursuit of knowledge, justice and human dignity. His contributions to academia, policy, institution-building and leadership have left an indelible mark on the continent and the world, and show the way for those committed to creating a more equitable and inclusive global society. His ideas and values will undoubtedly endure, shaping the work of scholars, policymakers and activists for generations to come. Conclusion Thandika Mkandawire was one of the most brilliant and inspiring individuals I have ever known. His prodigious intellect, sharp critiques of conventional development paradigms and unwavering commitment to Pan-Africanism deeply impressed me and countless others. Beyond his scholarly contributions, Thandika was a model public intellectual—principled, rigorous and deeply humane. He had a unique ability to distil complex ideas into clear, accessible insights, sparking intellectual curiosity and challenging lazy thinking. My encounters with him, whether in formal academic settings or in casual conversations, were always enriching. His infectious humour, boundless joy for life and unshakeable faith in Africa’s potential were a source of inspiration. Thandika’s mentorship played a crucial role in shaping my intellectual journey. Like many African scholars of my generation, I am deeply indebted to his leadership at CODESRIA, which provided critical support during the difficult decades of structural adjustment. My academic career was literally saved and turbocharged by CODESRIA’s Reflections on Development Fellowship funded by the Rockefeller Foundation, which I received in 1989. The fellowship enabled me to write A Modern Economic History of Africa, Volume 1: The Nineteenth Century, which was published by the CODESRIA Book Series in 1993. The book proceeded to win the Noma Award in 1994. Thandika proudly displayed the publisher’s plaque of the award in his office. Since then, I have published my most significant books with CODESRIA, including the latest book we will be launching after this address, Re-Envisioning the African and American Academies. Mkandawire’s legacy transcends his individual achievements; it lies in the vibrant intellectual communities he nurtured and the transformative ideas he championed. His life’s work remains a guiding light for those committed to the ongoing struggle for epistemic, economic and existential emancipation. Thank you, Thandika, for your extraordinary mind and enduring vision. THANK YOU!